ANALYSIS OF THE CURRENT STATE AND DEVELOPMENT OF THE DIGITAL ECONOMY IN KAZAKHSTAN - Francesco, Li Moli; Karlygash, Mukhtarova; A., Tovma N.; Kaurhan, Kazbekova; Karlygash, Akimbaeva (Farabi Journal of Social Sciences, 2020)
The purpose of the study is to review and conduct a scientific analysis of the current state and development of the digital economy of the Republic of Kazakhstan, which determine the existing and prospective potentials. Methodology-generalization, deductive approach, analytical comparisons, analysis and synthesis, statistical studies. Originality/value-analyzed and systematized modern parameters of the state, causing the formation of sustainable development of the economy of the Republic of Kazakhstan, which allows you to specify the reserves and priorities of the quality of economic growth. Conclusions − on the basis of the conducted research it is revealed that the current stage of the economy of the Republic of Kazakhstan requires a significant strengthening of the state policy to ensure its development, taking into account the trends of globalization of world economic policy, competition and scientific and technological progress. The analyzed quantitative and qualitative parameters of the economy showed that the main indicators of its growth do not correspond to the optimal level.